Clostridioides difficile infection and recurrence in cancer patients (CIRCA): A multicentre, international study - Pedro Puerta-Alcalde; Jessica O'Keefe; Rachel Woolstencroft; Shipraa Kaul; Néstor López; Katie Cronin; Andrew Lim; Nicole Garcia-Pouton; Míriam Álvarez; Lynette Chee; Mateu Espasa; Ignacio Grafia; et al. (International Journal of Infectious Diseases)
Objectives: We aimed to describe the characteristics of Clostridioides difficile infection (CDI) in cancer patients, analysing risk factors for 90-day recurrence and attributable mortality. Methods: Retrospective analysis on all CDI episodes from 2020 to 2022 in three Australian hospitals and one Spanish hospital. Logistic regression analyses were performed. Results: A total of 547 CDI episodes in cancer patients were documented. Treatment predominantly involved vancomycin (81.5%), followed by metronidazole (15.0%) and fidaxomicin (9.1%). Combined antibiotics were used in 61 (11.2%) episodes. The 90-day recurrence rate was 15.6%. Independent risk factors for CDI recurrence were female sex (OR 2.26, 95% CI 1.13-4.52), age >75 years (OR 2.69, 95% CI 1.30-5.59), dialysis (OR 5.15, 95% CI 1.45-18.27), vomiting at presentation (OR 0.06, 95% CI 0.01-0.55), colonic wall thickening in the CT abdomen (OR 2.42, 95% CI 1.06-5.49) and vancomycin therapy (OR 4.60, 95% CI 1.34-15.84). Overall, 90-day mortality was 22.3%, but attributable mortality was 4.9%. Risk factors for mortality attributed to CDI were age >65 years (OR 15.91, 95% CI 2.64-95.80), previous cerebrovascular disease (OR 20.27, 95% CI 3.12-131.84), antibiotic therapy within the last 30 days (OR 0.17, 95% CI 0.05-0.54), high-output diarrhoea (OR 6.68, 95% CI 1.68-26.56), high CRP-levels (OR 11.60, 95% CI 1.90-70.81) and need for treatment change (OR 6.65, 95% CI 2.20-20.08). Conclusions: CDI recurrence rates among cancer patients remain significant. Nonetheless, fidaxomicin and other preventive strategies are seldom used. We identified several factors that could inform the implementation of these strategies in cancer patients.